1994
DOI: 10.1007/bf02190377
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative EEG analysis at rest and during photic stimulation in drug-naive patients with first-episode paranoid schizophrenia

Abstract: In the present study, quantitative EEG analysis was performed at rest and during 10 Hz photic stimulation in 14 drug-naive patients with first-episode paranoid schizophrenia and 20 sex- and age-matched control subjects. Compared with the normal controls, the patients had significantly lower alpha-2 band amplitude in the resting EEG over all recording regions. No significant group differences were found in other frequency bands. In addition, EEG analysis during photic stimulation demonstrated that the patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 18 publications
0
19
0
3
Order By: Relevance
“…In a latter study, the investigators pointed out that the slow wave abnormality (mainly delta increase) is more or less localized to frontal lobe regions (28). A frontal localization of EEG abnormalities received support from a number of studies (24,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). A smaller number of studies found spectral EEG abnormalities to be localized to the more posterior regions of the brain (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…In a latter study, the investigators pointed out that the slow wave abnormality (mainly delta increase) is more or less localized to frontal lobe regions (28). A frontal localization of EEG abnormalities received support from a number of studies (24,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). A smaller number of studies found spectral EEG abnormalities to be localized to the more posterior regions of the brain (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…PDRs are commonly conducted in routine EEG examinations and have been validated as useful for investigating neurological disorders [14]. Recent studies of quantitative EEG analysis have shown abnormal PDRs in patients with DAT [15,16] and schizophrenia [17]. Although the neurochemical correlates of PDR generation are unclear, the thalamocortico-thalamic reverberating circuit is thought to participate in the development and maintenance of PDRs [18].…”
Section: Introductionmentioning
confidence: 99%
“…Такой тип изменений α-ритма согласуется с рядом исследова-ний параноидной шизофрении другими авторами, отме-чавшими диффузный характер ослабления этого ритма [14][15][16]. Несмотря на общую для обеих групп больных тенденцию ослабления α-ритма, изменения были выра-жены сильнее у больных с преобладанием позитивных расстройств, что предполагает сравнительно более высо-кий уровень активации коры у этих больных.…”
Section: Discussionunclassified
“…Применяли разработанный в лаборатории клини-ческой нейрофизиологии адаптивный метод определения частотных границ ритмов ЭЭГ [42]. С помощью этого ме-тода в частотной полосе 1-70 Гц было выделено 12 ча-стотных диапазонов (ритмы): δ (1,1-4,1 Гц), θ1 (4,1-6,1 Гц), θ2 (6,1-8,1 Гц), α1 (8,1-9,8 Гц), α2 (9,(8)(9)(10)(11)4 Гц), α3 (11,4-13,0 Гц), β1 (13,0-15,6 Гц), β2 (15,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20),0 Гц), β3 (20,0-24,4 Гц), β4 (24,7 Гц), γ1 (30,7-48,8 Гц), γ2 (Гц 51,0-57,7). Полученные диапазоны отражали адек-ватное исследуемой выборке и состояниям деление спек-тра ЭЭГ на независимые, мало коррелированные ритмы, что оптимизировало количество необходимых для иссле-дования показателей.…”
Section: материал и методыunclassified
See 1 more Smart Citation